El derecho a la igualdad laboral para la contratación de personas con discapacidad en el GAD municipal de Guaranda periodo 2021 - Rumipamba Yantalema, Juan Daniel (2023)
After the creation and promulgation of the Constitution of the Republic in 2008, a constitution very different from the others; guarantor of rights and social justice which is committed to promoting public policies for the benefit of people with disabilities in the field of the right to work and equal opportunities. Labor Law is fundamental in the life of each person, this must be in conditions: equitable, equal opportunities, decent, satisfactory remuneration and their respective protection against discrimination; which will contribute to cover basic needs by itself, resulting in a better and more dignified life. People with disabilities are considered a priority attention group as ratified by the Constitution of the Republic of Ecuador; the State will be the guarantor of insertion into the labor field in public or private entities without any discrimination and equal opportunities, according to their skills, academic degree and abilities; which will be a top priority. The present work will focus on investigating the violation of the right to labor equality for the hiring of people with disabilities in the Guarana Municipal GAD and identifying the different causes, the lack of different improvements of public policies that limit labor insertion and therefore how the rules guarantee the right to work for people with disabilities. In the same way, the type of methodology applied in the present research work is the quantitative and qualitative method since it helped to examine two data and to know the real situation obtained with the surveys carried out of the total number of workers with disabilities who provide their service. in the GAD Municipality of Guaranda. Likewise, the type of research used in the work is descriptive, explanatory and documentary, techniques and research instrumentation such as observation and survey were also used. With the study and the results obtained, to be able to raise awareness and suggest the changes that must be made to improve the lives of people with disabilities in the field of obtaining decent and safe work. Keywords: Right to Equality, Public Policies, (PCD) Persons with Disabilities, Labor Hiring, Vulneration